Etiologi dan Penegakan Diagnosis Disfagia - Ni Komang Devi Wiratningrum; Imanto, Mukhlis (Medula, 2024)
Dysphagia or complaints of difficulty swallowing is a problem that can occur in all age group, however, the incidence of dysphagia tends to be higher in the age group over 50 years, with a prevalence of around 7-22% of the total population in the world. Misidentification and the assumption that dysphagia symptoms are a process normal aging means many seniors do not seek medical help. Even though the prevalence of dysphagia is quite high, until now there is no data regarding the prevalence of dysphagia in Indonesia. The classification of dysphagia based on etiology is divided into three, namely mechanical dysphagia due to obstruction, motor dysphagia due to neuromuscular disorders and dysphagia caused by emotional disorders. The diagnosis of dysphagia is carried out using anamnesis, physical examination and supporting examinations such as Video Fluooscopy Swallow Assessment (VFSS), Flexible Endoscopy Evaluation of Shallowing (FEES), radiology, esophagoscopy and manometrics. Management that can be carried out for individuals with symptoms of dysphagia is postural techniques, modification of food patterns and textures, and maneuver techniques.